Levantamento florístico em remanescente de floresta ripária no alto rio Paraná: Mata do Araldo, Porto Rico, Paraná, Brasil - De Souza, Maria Conceição; Monteiro, Reinaldo [UNESP] (Universidade Estadual de Maringa, 2005)
The purpose of this study was to realize a floristic survey in riparian forest remains of the Upper Paraná River, under domain of the submontane seasonal semideciduous forest, located in Porto Rico, Paraná, Brazil (53°19'3 W e 22°47'37 S). Within and in the neighborhood of 10.000 m2 area (100 m × 100 m), 165 species were surveyed, in 124 genera and 60 families, distributed in arboreous, shrubs, herbs, climbers and hemiparasites. Leguminosae, Myrtaceae, Poaceae, Rubiaceae, and Bignoniaceae were the families with the highest species' richness, showing together 33.33%, and the genera more representative were Eugenia, Casearia, Guarea, Inga, Panicum, and Solanum, with 12.73% of the species. Though the perturbations verified in the forest remains, eight species were rare for this type of vegetation and 12 were listed as fishes natural food.
Floristic survey in riparian forest remains of the upper Paraná River: Mata do Araldo, Porto Rico, Paraná, Brazil
Keywords: Floristic survey; Paraná River; Riparian forest; Bignoniaceae; Brazil; Casearia; Eugenia; flora; forest; herb; legume; millet; Myrtaceae; nonhuman; Poaceae; river; Rubiaceae; Solanum; species composition; woody stem; Fabaceae; Guarea; Inga; Panicum; Pisces